Influence of FLG loss-of-function mutations in host–microbe interactions during atopic skin inflammation. Issue 3 (June 2022) - Oláh, Peter; Szlávicz, Eszter; Kuchner, Marcus; Nemmer, Jana; Zeeuwen, Patrick; Lefèvre-Utile, Alain; Fyhrquist, Nanna; Prast-Nielsen, Stefanie; Skoog, Tiina; Serra, Angela; Rodríguez, Elke; Raap, Ulrike; et al.
Abstract: Background: Loss-of-function mutations in the filaggrin ( FLG ) gene directly alter skin barrier function and critically influence atopic inflammation. While skin barrier dysfunction, Th2-associated inflammation and bacterial dysbiosis are well-known characteristics of atopic dermatitis (AD), the mechanisms interconnecting genotype, transcriptome and microbiome remain largely elusive. Objective: In-depth analysis of FLG genotype-associated skin gene expression alterations and host-microbe interactions in AD. Methods: Multi-omics characterization of a cohort of AD patients carrying heterozygous loss-of-function mutations in the FLG gene (AD Mut ) (n = 15), along with matched wild-type (AD Wt ) patients and healthy controls. Detailed clinical characterization, microarray gene expression and 16 S rRNA-based microbial marker gene data were generated and analyzed. Results: In the context of filaggrin dysfunction, the transcriptome was characterized by dysregulation of barrier function and water homeostasis, while the lesional skin of AD Wt demonstrated the specific upregulation of pro-inflammatory cytokines and T-cell proliferation. S. aureus dominated the microbiome in both patient groups, however, shifting microbial communities could be observed when comparing healthy with non-lesional AD Wt or AD Mut skin, offering the opportunity to identify microbe-associated transcriptomic signatures. Moreover, an AD core signature with 28 genes, including CCL13, CCL18, BTC, SCIN, RAB31 and PCLO was identified. Conclusions: Our integrative approach provides molecular insights for the concept that FLG loss-of-function mutations are a genetic shortcut to atopic inflammation and unravels the complex interplay between genotype, transcriptome and microbiome in the human holobiont. Highlights: Eczema patients carrying filaggrin mutations present equal or moderately higher severity than matched wild-type patients. More extensive dysregulation of gene expression is present in filaggrin Wt lesions than in filaggrin Mut A lower threshold of onset in filaggrin Mut and a „longer route" required for the same manifestation in filaggrin Wt .